(untitled) (ENTHYMEMA, 2013)
Although the field of narratology is increasingly diversified with the appearance of various new approaches and new models, it has more elements of consolidation than the picture appears to be. I will discuss three aspects of consolidation: (1) how postclassical narratologies consolidate classical narrative poetics; (2) how the cognitive approach to unreliability consolidates the rhetorical criterion of unreliability and, moreover, how the rhetorical approach consolidates the cognitive concern with individual readers; and (3) how the Chinese classification of modes of discourse presentation consolidates its Western counterpart.